Skin - Vrettos, Adrienne Maria (New York : Simon Pulse, 2006)
When his parents decide to separate, eighth-grader Donnie watches with horror as the physical condition of his sixteen-year old sister, Karen, deteriorates due to an eating disorder.
Accelerated Reader AR
Keywords: Brothers and sisters -- Fiction; Anorexia nervosa -- Fiction; Family problems -- Fiction; Self-perception -- Fiction